Effect of a Bacillus probiotic strain on Nellore cattle finished on pasture during the dry season - Calaca, A. M.M.; Figueiredo, C. B.; Silva, M. B.; Fernandes, J. J.R.; Fernandes, M. H.M.R. [UNESP]; Silva, L. F.; Couto, V. R.M. (Elsevier, 2022)
The objective of this study was to evaluate the productive performance of Nellore bulls raised under grazing conditions during the dry season and fed a diet supplemented with a Bacillus probiotic strain, and its influence on ruminal and intestinal mucosa development. In addition, the probiotic effects on digestibility and ruminal fermentation were determined. The experiment was conducted between July and November 2017, corresponding to the dry period in the state of Goias, Brazil. Eighty-four animals (approximately 24 months old) were included in the study. Four animals were randomly slaughtered at the beginning of the experiment to assess carcass yield. The remaining animals (80 Nellore bulls, initial body weight (BW) of 354 ± 3.4 kg) were blocked based on their initial BW and assigned to one of two treatments: concentrate with probiotics and concentrate without probiotics (control). Bulls were divided into 16 paddocks of palisade grass (Urochloa brizantha spp.) pasture, supplemented with concentrate at 2% BW. After 133 days, the animals were slaughtered, and carcass traits were measured. Tissues from the ruminal ventral sac and jejunum were collected to evaluate the morphology of the rumen papillae and intestinal villi. No differences were detected in performance data; a tendency was found in improving the dressing percentage, carcass average daily gain (ADG), and gain to feed ratio based on carcass ADG. The 12th rib fat thickness was significantly lower in animals fed probiotic than in control group (4.06 vs. 2.97 mm, p < 0.05). No significant effect on the development of the ruminal and intestinal epithelia was observed with the use of probiotics. Later, an in vivo digestibility trial was carried out to investigate the influence of the Bacillus probiotic strain on rumen fermentation, with the same treatments, using eight rumen-cannulated steers in a cross-over design. Fecal output and forage intake were estimated using titanium dioxide and indigestible neutral detergent fiber (iNDF), respectively. Administration of the probiotics did not improve dry matter (DM) intake or nutrient digestibility. Isovalerate levels were higher in animals fed probiotics (2.01 vs. 1.55, p < 0.05), and no other differences were observed in the rumen fermentation parameters. The tested Bacillus probiotic strain significantly reduced carcass fat deposition in Nellore bulls finished in tropical grass pastures supplemented with a high-concentrate diet during the dry season.
Keywords: Additives; Bacillus, Probiotic; Beef cattle; Grazing; Supplementation